On the trapline - Robertson, David, 1977- (Tundra Books, 2021)
A picture book celebrating Indigenous culture and traditions. The Governor General Award-winning team behind When We Were Alone shares a story that honors our connections to our past and our grandfathers and fathers. A boy and Moshom, his grandpa, take a trip together to visit a place of great meaning to Moshom. A trapline is where people hunt and live off the land, and it was where Moshom grew up. As they embark on their northern journey, the child repeatedly asks his grandfather, "Is this your trapline?" Along the way, the boy finds himself imagining what life was like two generations ago -- a life that appears to be both different from and similar to his life now. This is a heartfelt story about memory, imagination and intergenerational connection that perfectly captures the experience of a young child's wonder as he is introduced to places and stories that hold meaning for his family.--Amazon.